Thank you for the opportunity to help you with your question!
Use the formula of the differenceof cubes which is: a^3 - b^3 = (a - b)(a^2 + ab + b^2).
So we compare the given expression x^3 - 8 to the left side of the formula: a^3 - b^3.
Here, we can see: a^3 = x^3 and b^3 = 8. So we solve each equation by taking the cube root like this:
3th root(a^3) = 3th root(x^3) ---------> a = x
3th root(b^3) = 3th root(8) ------------> b = 2 (the cubic root of 8 is 2 since 2*2*2 = 8).
Then we enter x in place of a and 2 in place of b into the right side of the formula like this:
(a - b)(a^2 + ab + b^2) = (x - 2)(x^2 + 2x + 2^2) = (x - 2)(x^2 + 2x + 4) since 2^2 = 2*2 = 4.
So x^3 - 8 = (x - 2)(x^2 + 2x + 4).
Please let me know if you need any clarification. I'm always happy to answer your questions.
15 Million Students Helped!
Sign up to view the full answer